Optimizing Zakat Management: The Agricultural Sector’s Role in Poverty Reduction in Indonesia and Malaysia - Mukhlis, Mukhlis; Zaimsyah, Annisa Masruri; Ibrahim, Patmawati Bte Hj; Marliyah, Marliyah; Siregar, Pani Akhiruddin (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2023)
The development of welfare systems and income tax in the 20th century shows religious practices in poverty alleviation, especially zakat in Islamic tradition. In Indonesia and Malaysia, zakat management is an effort in poverty alleviation, but challenges remain, especially in the centralized system in Malaysia. This study aims to examine the effectiveness of agricultural zakat management in Indonesia and Malaysia, including comparing its implementation and impact in the agricultural sector. This study uses a qualitative method, using a comprehensive literature review and content analysis based on Creswell's qualitative research framework. The results of this study indicate that agricultural Zakat has significant potential to increase zakat income and support poverty alleviation. In Indonesia, where agriculture is a major economic sector, the impact is very prominent. However, better governance and digital integration are needed for optimization. Collaboration between the government, zakat institutions, and the community is essential in order to maximize the role of zakat in economic empowerment. This study contributes to the comparative analysis of zakat management in the two countries and highlights the need for local strategies to increase its effectiveness in poverty alleviation.